Rosana Vaca, Las reglas de la caridad. Las damas de Caridad de San Vicente de Paúl. Buenos Aires (1866-1910) (Rosario: Prohistoria, 2013), 168 pp. (2015)
Las reglas de la caridad. Las damas de Caridad de San Vicente de Paúl. Buenos Aires (1866-1910)